ISOLASI DAN PENENTUAN KONDISI KERJA OPTIMUM AMILASE DARI TALAS BOGOR (Colocasia esculenta (L.) shoot) - Rezky Estrada; Rudi Kartika; Winni Astuti (PROSIDING SEMINAR KIMIA, 2018)
Isolation and determination of optimum amylase work condition has been conducted from Bogor taro (Colocasia esculenta (L.) shoot). The aim of this research is to understand the optimum work condition and specific activity of amylase from Bogor taro. Amylase was isolated using homogenization techniques and sentrifugation. The raw extract of enzyme that contain amylase produced by Bogor taro then used to determine the total protein concentration and tested its activity in pH condition, temperature and maximum substrate concentration in various ways. The determination of total protein concentration was done with Bradford method, while the optimum work condition and specifik activity of amylase was done with dinitrosalycylic acid (DNS) method. The result of this reseach show the total protein concentration in Bogor taro is 7,88 μg/mL. Optimum work condition in Bogor taro is on acidity level (pH) 6, 600C temperature and 6 mg/mL substrate concentration. Specific activity from Bogor taro is 9573,68 U/mL. Keywords: amylase, taro tuber Bogor (Colocasia esculenta (L.) shoot), specific activity of amylase.